Sex differences in contextual fear conditioning and extinction after acute and chronic nicotine treatment - Keady, Jack V.; Hessing, Marissa C.; Songrady, Judy C.; McLaurin, Kristen; Turner, Jill R. (Biology of sex differences, 2024)
Chronic cigarette smokers report withdrawal symptomology, including affective dysfunction and cognitive deficits. While there are studies demonstrating sex specific withdrawal symptomology in nicotine-dependent individuals, literature examining the underlying biological mediators of this is scant and not in complete agreement. Therefore, in this study, we evaluated the sex specific effects of nicotine and withdrawal on contextual fear memory, a hippocampally dependent aspect of cognition that is disrupted in nicotine withdrawal. Male and female B6/129F1 mice (8-13 weeks old) were used in all experiments. For the acute nicotine experiment, mice received intraperitoneal saline or nicotine (0.5 mg/kg) prior to contextual fear conditioning and test. For the chronic nicotine experiment, mice received nicotine (18 mg/kg/day) or saline for 11 days, then underwent contextual fear conditioning and test. Following the test, mice underwent minipump removal to elicit withdrawal or sham surgery, followed by the fear extinction assay. Bulk cortical tissue was used to determine nicotinic acetylcholine receptor levels via single point [ H]Epibatidine binding assay. Gene expression levels in the dorsal and ventral hippocampus were quantified via RT-PCR. We found that female mice had a stronger expression of contextual fear memory than their male counterparts. Further, following acute nicotine treatment, male, but not female, subjects demonstrated augmented contextual fear memory expression. In contrast, no significant effects of chronic nicotine treatment on fear conditioning were observed in either sex. When examining extinction of fear learning, we observed that female mice withdrawn from nicotine displayed impaired extinction learning, but no effect was observed in males. Nicotine withdrawal caused similar suppression of fosb, cfos, and bdnf, our proxy for neuronal activation and plasticity changes, in the dorsal and ventral hippocampus of both sexes. Additionally, we found that ventral hippocampus erbb4 expression, a gene implicated in smoking cessation outcomes, was elevated in both sexes following nicotine withdrawal. Despite the similar impacts of nicotine withdrawal on gene expression levels, fosb, cfos, bdnf and erbb4 levels in the ventral hippocampus were predictive of delays in female extinction learning alone. This suggests sex specific dysfunction in hippocampal circuitry may contribute to female specific nicotine withdrawal induced deficits in extinction learning.